2001
DOI: 10.1021/bp010056c
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Step in the Biological Degradation of a Textile Dye

Abstract: This research documents the removal of the dye Gris Lanaset G from aqueous solutions by fungal pellets. Adsorption of the dye by dead biomass pellets of Trametes versicolor was determined and compared with dye removal by enzymatic degradation. Six kinetic equations were fitted to the experimental adsorption data obtained. The results indicate that kinetics such as the Elovich equation, which considers that the rate-controlling step is the diffusion of the dye molecules, show the best fit. Nonlinear Langmuir an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 14 publications
4
19
0
Order By: Relevance
“…Further, the UV-Vis spectra of the effluent also indicated that dye removal in the initial days was due to adsorption (UV-Vis absorbance spectra not shown). Similar observations have been made by Aretxaga et al [20] while conducting experiments with live and dead biomass pellets of Trametes versicolor. It was observed that adsorption played an important role and accounted for around 80% of colour elimination.…”
Section: Methane Productionsupporting
confidence: 83%
“…Further, the UV-Vis spectra of the effluent also indicated that dye removal in the initial days was due to adsorption (UV-Vis absorbance spectra not shown). Similar observations have been made by Aretxaga et al [20] while conducting experiments with live and dead biomass pellets of Trametes versicolor. It was observed that adsorption played an important role and accounted for around 80% of colour elimination.…”
Section: Methane Productionsupporting
confidence: 83%
“…Among five different kinetic models, two kinetic models such as the pseudo second order and parabolic diffusion kinetic models had very high determination coefficients (R 2 ). The pseudo second order kinetic model is usually related to the adsorption process that has the exchange reaction as the rate-controlling step (Aretxaga et al, 2001). Therefore, it was found that the exchange reaction in which arsenate adsorption for adsorbents resulted in OH -/H + release was the rate-controlling step for these kinetic studies.…”
Section: Arsenic Adsorption Isothermmentioning
confidence: 99%
“…Biosorption is a physicochemical process involving many mechanisms, including absorption, adsorption, ion exchange, surface complexation and precipitation. Biosorption processes are highly important in the environment and conventional biotreatment processes (Ali 2010(Ali , 2012(Ali , 2014Ali et al 2012;Ali and Gupta 2007;Aretxage et al 2001;Fomina and Gadd 2014). In recent years, there has been an increasing interest in the ligninolytic capabilities of microfungi, which, similarly to the white-rot fungi, can remove a broad spectrum of aromatic compounds from wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…However, decolorization with active biomass provides better results, most likely due to the parallel dye compound removal (Aretxage et al 2001). By using the growing cultures in dye removal, one can avoid the need for a separate biomass production process, including cultivation, harvesting, drying, processing and storage prior to use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation